Peningkatan motivasi dan hasil belajar matematika melalui model pembelajaran team games tournament siswa kelas iv sd - Ernamasari, Navalia Dewi; Riyadi, Riyadi; Wahyuningsih, Siti (Universitas Sebelas Maret, 2024)
The purpose of this study was to increase the motivation and learning outcomes of mathematics in class IVB students at SD Djama'atul Ichwan Surakarta, especially in area and volume measurement materials. This research is included in the type of classroom action research. Sources of research data were obtained from students (learning outcomes and learning motivation), teachers (teacher performance in applying the team games tournament model), documents (student learning outcomes in the last exam, syllabus, teaching modules). Data collection was done through interview, observation, questionnaire, and test techniques. The data obtained were analyzed using techniques by Miles and Huberman. The results of this study are the Team Games Tournament learning model which is carried out through the stages of class presentation, learning in groups, games, matches, and awards can increase student motivation and learning outcomes in area and volume measurement math lessons. The percentage of students in the category of having very high motivation always increases every cycle. The results of the student motivation questionnaire always increased, starting from 40.75% in the pre- stage, to 66.66% in cycle I, and increased again in Cycle II to 80.77%. Furthermore, the evaluation of student learning outcomes with the percentage of student completeness increased from 18% in preaction, to 46% in Cycle I, and to 70.335% of students completed in Cycle II.